2012
DOI: 10.4168/aair.2012.4.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adipokines and Hormones of Obesity in Childhood Asthma

Abstract: PurposeThe aim of this study was to evaluate serum levels of leptin, ghrelin, and adiponectin in obese and non-obese children with asthma and in healthy non-asthmatic children, and analyze their relationships with clinical outcomes.MethodsThis study enrolled 40 obese and 51 non-obese children with asthma and 20 healthy children. Body mass index and serum leptin, ghrelin, and adiponectin levels were determined in all children. Asthma symptom scores and lung function test results were recorded for subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
7
60
1
3
Order By: Relevance
“…Our findings corroborate those of Yuksel et al, who concluded that leptin plays a role in the severity of asthma in children. (30) Our data support the hypothesis that obese patients with asthma exhibit Th1 polarization, whereas lean patients with asthma exhibit Th2 polarization, and that IFN-γ might be a pathway in the process of leptin-induced inflammation. This suggests that, in obese subjects with asthma, Th1 polarization might be modulated more by obesity and less by asthma itself, and this is supported by the lack of correlation between leptin and IFN-γ levels and between leptin and IgE levels in obese children with asthma.…”
Section: Resultssupporting
confidence: 86%
“…Our findings corroborate those of Yuksel et al, who concluded that leptin plays a role in the severity of asthma in children. (30) Our data support the hypothesis that obese patients with asthma exhibit Th1 polarization, whereas lean patients with asthma exhibit Th2 polarization, and that IFN-γ might be a pathway in the process of leptin-induced inflammation. This suggests that, in obese subjects with asthma, Th1 polarization might be modulated more by obesity and less by asthma itself, and this is supported by the lack of correlation between leptin and IFN-γ levels and between leptin and IgE levels in obese children with asthma.…”
Section: Resultssupporting
confidence: 86%
“…The p value of the ghrelin levels was >0.05; however, the small number of subjects evaluated in this study might have prevented us from finding a significant difference. Yuksel et al reported that the levels of ghrelin are decreased in children with asthma [15]. They surmised that ghrelin competes against IgE, IL-6 and TNF-α, which may affect the development of asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Although asthma is similar to COPD in particular in terms of chronic respiratory inflammation, it has been reported that the adiponectin levels are decreased in children with asthma [15]. Sood et al demonstrated that adults with the histories of asthma have lower mean unadjusted serum adiponectin concentrations than those without asthma [16,17].…”
mentioning
confidence: 99%
“…Surely, some part of the link can be explained by overestimation due to fat mass on the thoracic chest mimicking asthma symptoms (65) ; part of the weight increase may also be due to medication or decreased activity caused by exercise-induced wheezing attacks, resulting in reverse causation (61) . There is no doubt that the endocrine role of adipose tissue (adipokines) is a strong physiological link and very plausibly could be a mechanism in causing a chain of disruption leading to inflammation and narrowing of airways (98,(105)(106)(107) . Despite existing evidence indicating that adipokines may be a plausible link between obesity and asthma, clinical studies bring inconclusive results.…”
Section: Possible Linksmentioning
confidence: 99%